2020
DOI: 10.1016/j.ajog.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) and pregnancy: what obstetricians need to know

Abstract: Word Count: 497 27 28 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
814
1
95

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 965 publications
(923 citation statements)
references
References 46 publications
13
814
1
95
Order By: Relevance
“…Interestingly, and in line with the pattern of COVID-19 producing milder symptoms in children, there is currently no evidence for increased risk of severe outcomes of COVID-19 in pregnant women. We should note, though, that this evidence is based on limited data, while reports from SARS-CoV, MERS-CoV and from other respiratory infections suggest these conclusions are premature and pregnant women could be at risk of a severe course of COVID-19 (Rasmussen et al, 2020). If, however, pregnancy proves to provide some protection from disease severity, it could offer unique opportunities for the development of therapeutic solutions.…”
Section: One Size Does Not Fit Allmentioning
confidence: 92%
“…Interestingly, and in line with the pattern of COVID-19 producing milder symptoms in children, there is currently no evidence for increased risk of severe outcomes of COVID-19 in pregnant women. We should note, though, that this evidence is based on limited data, while reports from SARS-CoV, MERS-CoV and from other respiratory infections suggest these conclusions are premature and pregnant women could be at risk of a severe course of COVID-19 (Rasmussen et al, 2020). If, however, pregnancy proves to provide some protection from disease severity, it could offer unique opportunities for the development of therapeutic solutions.…”
Section: One Size Does Not Fit Allmentioning
confidence: 92%
“…Since there is substantial overlap between the clinical presentation of worsening asthma and COVID-19 and increasing community spread lessens likelihood of known contact with a case, screening for COVID-19 is required if available in any asthmatic child who comes to medical attention with worsening cough or shortness of breath. (8,13)…”
Section: Differentiating Asthma From Covid-19mentioning
confidence: 99%
“…(10,11) It is further reassuring that children appear to be at lower risk of COVID-19 morbidity and mortality than the adult population in general, although severe infection still can occur. (13,20) The CDC morbidity and mortality report notes that among the 149,082 reported U.S. cases of COVID-19 for which age is known, only 2572 (1.7%) occurred in In summary, based on available information to date, it is unclear whether there is a significantly increased risk of COVID-19 morbidity among asthmatic children. (8,9) It is also unknown whether asthma medications such as high-dose inhaled corticosteroids or asthma biological therapies pose a risk in managing COVID-19 infections.…”
Section: The Role Of Asthma In Covid-19 Morbidity and Mortalitymentioning
confidence: 99%
“…Previous studies demonstrated that SARS infection during pregnancy is associated with adverse maternal and neonatal complications including spontaneous miscarriage, preterm delivery, intrauterine growth restriction, undergoing endotracheal intubation, admission to the intensive care unit, renal failure, and disseminated intravascular coagulopathy (8).…”
mentioning
confidence: 99%